Different Dynamics of Aquaporin 4 and Glutamate Transporter‐1 Distribution in the Perineuronal and Perivascular Compartments during Ischemic Stroke. (29th April 2014) - Mogoanta, Laurentiu; Ciurea, Marius; Pirici, Ionica; Margaritescu, Claudiu; Simionescu, Cristiana; Ion, Daniela A.; Pirici, Daniel
Abstract Aquaporin‐4 (AQP4) and glutamate transporter‐1 (GLT‐1) represent the major water and glutamate astrocyte buffering gateways in the brain. Utilizing perilesional ischemic human cortices, we have performed here for the first time an integrative assessment on both AQP4 and GLT‐1, and on their proximity to blood vessels and neurons. Counting the relative number of AQP4±/GLT‐1±/glial fibrillary acidic protein± cells showed that double‐positive variants were overall most frequent, and their number tended to decrease from organized and recent perilesional cortices to controls. AQP4/GLT‐1 colocalization showed higher coefficients for the perilesional cortices compared with controls, suggesting an increased water/glutamate‐buffering capability. Distance frequency analysis of AQP4/GLT‐1 in relationship to neurons showed that both markers were concentrated at 20–40 μm around the perikarya; with AQP4 being more abundant in close proximity, these differences were not being driven by changes in neuropil density alone. Our study suggests a dual, simultaneous astrocytic function depending on the relative distance to neurons and vessels, with increased water and glutamate‐buffering capability in the mid perineuronal space, and an increased water‐buffering capability in the immediate perineuronal space, even higher than around vessels. Thus, adding specific AQP4/GLT‐1 modulator agents selectively depending on the acute/chronic phase of stroke might increase the efficacy of existing treatments.